Emotion profiles of university students engaging in non-suicidal self-injury: Association with functions of self-injury and other mental health concerns - Christoforou, R.; Boyes, Mark; Hasking, Penelope (ELSEVIER IRELAND LTD, 2021)
We investigated emotion profiles among undergraduate students with lived experience of non-suicidal self-injury (NSSI) and their associations with different NSSI functions and other dysregulated behaviors, including risky drinking, symptoms of borderline personality disorder, eating disorders, anxiety, depression, and stress. A sample of 270 undergraduate students (84% female, Mage = 21.5 years) with a history of self-injury completed well-validated measures of self-injury, emotion regulation, alexithymia, coping strategies and of other dysregulated behaviors. A K-means cluster analysis was conducted to extract emotion profiles from the data. Analyses of variance were used to test associations between emotion profiles, demographic factors, functions of NSSI and comorbid dysregulated behaviors. A three-cluster solution was supported. Similar characteristics were presented regarding difficulties in emotion regulation and alexithymia between the considerate emotion difficulties and the passive moderate emotion difficulties groups, although they demonstrated different associations with the functions of NSSI and other dysregulating behaviors. This emphasizes the importance of investigating the type of coping strategies used during functional assessment to inform future treatment. The group reporting no emotion difficulties engaged in more adaptive coping strategies compared to the others. These emotion profiles and their association with NSSI functions could be used to develop more person-centered interventions for NSSI.